Keep the lights burning, Abbie - Roop, Peter; Roop, Connie; Adamson, Rick. (Ancramdale, NY : Live Oak Media, 1985)
In the winter of 1856, a storm delays the lighthouse keeper's return to an island off the coast of Maine, and his daughter Abbie must keep the lights burning by herself.
Track 1: 10:13 (Narration with page turn signals) ; Track 2: 10:00 (Narration with no page turn signals).
Read by Rick Adamson.
edited hb 2015-06-16
Keywords: Burgess, Abbie -- Juvenile literature; Burgess, Abbie; Matinicus Rock Lighthouse (Matinicus Rock, Me.) -- Juvenile literature; Matinicus Rock Lighthouse (Matinicus Rock, Me.); Lighthouse keepers -- Maine -- Biography -- Juvenile literature; Lighthouse keepers; Children's audiobooks; Compact discs